Pengaruh Kecemasan Siswa dalam Pemberian Sudden Mathematics Quiz pada Materi SPLDV Kelas VIII - Adinda Putri Iffatuz Zahroh; Welhelmi Klali; Nonik Indrawatiningsih (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to determine the effect of student anxiety on the administration of sudden mathematics quiz on the material of System of Linear Equations Two Variables (SPLDV) in class VIII Widya Darma Junior High School. The research used a quantitative approach with instruments in the form of a quiz to measure students' understanding of SPLDV and a math anxiety questionnaire to determine students' anxiety levels before and after giving sudden quizzes. The research sample consisted of 38 students from class VIII and the data were analyzed using simple linear regression test to determine the effect of anxiety with sudden mathematics quiz. The results showed that there was an effect of anxiety on student learning outcomes with the regression equation obtained was Y = 33.068 + 0.42X. From this equation, it is known that the constant (intercept) of 33.068 estimates the level of student anxiety (Y) on student grades (X) is zero which indicates a positive and unidirectional relationship between student grades and anxiety levels. This indicates that the higher the level of math anxiety, the lower the student learning outcomes. From the questionnaire results, it was found that most students experienced anxiety symptoms such as nervousness (34.4%), panic because they did not have time to study (28.1%), difficulty concentrating (43.8%), and fear of making mistakes (46.9%). This anxiety has an impact on cognitive impairment that hinders the completion of math problems.